Synthesis of TiO2 nanotubes by using combination of sonication and hydrothermal treatment and their photocatalytic activity for hydrogen evolution - Indar Kustiningsih; S Slamet; Widodo Wahyu Purwanto (Reaktor, 2015)
Effect of sonication and hydrothermal treatments on the synthesized of Titania nanotubes (TiO2 NT)has been investigated. Sonication of TiO2 P25 sol was performed using ultrasonic probe for certain time followed by hydrothermal treatment in a teflon lined stainless steel autoclave. The samples were characterized by means of X-ray powder diffractometer (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), UV-vis diffuse reflectance spectroscopy (UV-vis DRS) and Brunauer-Emmett-Teller (BET).The photocatalytic activity of prepared samples was evaluated with photocatalytic H2 evolution from aqueous methanol solution. The result showed that TiO2 NT was formed rapidly along with the duration of sonication treatment but the longer processing time of it would destroy the morphology of TiO2 NT. The optimal sonication time for the TiO2 NT formation was 10 min. It was obtained TiO2 NT with high crystallinity, high surface area and a perfect nanotubes structure.  Hydrogen production by using this sample was about two times higher than TiO2 P25 nanoparticle.   Keywords : TiO2 nanotubes, sonication, hydrothermal, hydrogen   Abstrak   Efek kombinasi proses sonikasi dan hidrotermal pada pembentukan TiO2 nanotubes telah dilakukan. TiO2 P25 disonikasi menggunakan ultrasonik probe dengan waktu tertentu kemudian dilanjutkan dengan proses hidrotermal di autoklaf berbahan teflon dan stainless steel. Sampel yang diperoleh di karakteriksasi menggunakan X-ray powder diffractometer (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), UV-vis diffuse reflectance spectroscopy (UV-vis DRS) and Brunauer-Emmett-Teller (BET). Aktifitas fotokatalis dari sampel diuji untuk produksi hidrogen dari larutan metanol. Dari hasil yang diperoleh TiO2 nanotubes lebih cepat terbentuk dengan adanya proses sonikasi, akan tetapi semakin lama waktu sonikasi bentuk nanotubes yang diperoleh menjadi rusak. Waktu optimal untuk proses sonikasi adalah 10 menit. Pada kondisi ini TiO2 yang terbentuk memiliki kristalinitas dan luas permukaan tinggi serta bentuk nanotubes yang sempurna. Produksi hidrogen pada kondisi inipun dua kali lebih besar dibandingkan dengan TiO2 P25 nano partikel.   Kata Kunci : TiO2 nanotubes, sonikasi, hidrotermal, hidrogen